Powder for annealing separator and method for producing the same, and method for producing grain-oriented electrical steel sheet

By optimizing the atmosphere breathability between the steel coil layers and using magnesium oxide annealing separator powder, the problems of poor film uniformity and insufficient impurity purification in the manufacturing of orientation electromagnetic steel plates are solved, and the effects of excellent magnetic characteristics and reduced production cost are achieved.

CN116133989BActive Publication Date: 2025-02-18JFE STEEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180052365.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-28
Filing Date
2021-08-25
Publication Date
2025-02-18
Estimated Expiration
2041-08-25

AI Technical Summary

Technical Problem

In the manufacturing of oriented electromagnetic steel plates, the magnetic characteristics are affected in the production of oriented electromagnetic steel plates, resulting in poor uniformity of forsterite films and insufficient purification of impurities such as nitrogen and sulfur due to insufficient air permeability between the steel coils.

Method used

By optimizing the atmosphere breathability between the steel coil layers, the specific method is to use an annealing separator powder with magnesium oxide as the main component, and its nitrogen permeability is controlled within the range of 0.020cm/s to 0.50cm/s to ensure secondary recrystallization The atmosphere before the start of the air permeability is appropriate, which promotes the uniformity of the forsteroid film and the purification of impurities.

Benefits of technology

In the manufacturing of oriented electromagnetic steel sheets, the results of good uniformity of the coating, good impurities purification and excellent magnetic properties are achieved, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005042753520000041
    Figure GDA0005042753520000041
  • Figure GDA0005042753520000042
    Figure GDA0005042753520000042
  • Figure GDA0005042753520000061
    Figure GDA0005042753520000061
Patent Text Reader

Abstract

The present invention provides a powder for annealing separator for grain-oriented electrical steel sheets, which can obtain grain-oriented electrical steel sheets with good impurity purification and excellent magnetic properties. The powder for annealing separator contains magnesium oxide as a main component, and has a nitrogen permeability of 0.020 cm / s to 0.50 cm / s when applied between steel sheets before the start of secondary recrystallization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a powder containing magnesium oxide as a main component used as an annealing separator in the production of a grain-oriented electrical steel sheet. Specifically, the present invention relates to a powder for an annealing separator capable of solving the problems of uneven film appearance caused by insufficient gas permeability between steel coil layers and insufficient removal (insufficient purification) of components that need to be purified (removed) from steel, such as nitrogen and sulfur, which have been problems in the past in steel coil annealing. Background Art

[0002] The production of grain-oriented electrical steel sheets generally involves hot rolling, annealing, cold rolling of steel billets adjusted to a specified composition, and further recrystallization annealing followed by final annealing. In addition, generally speaking, primary recrystallization annealing also serves as decarburization annealing, and final annealing also serves as secondary recrystallization annealing. Among the above processes, the final annealing process needs to be processed at a high temperature of more than 1200°C, so in order to prevent the steel coil from sticking, an annealing separator with magnesium oxide powder as the main component is usually applied to the surface of the steel sheet.

[0003] Here, magnesium oxide, in addition to the role of the above-mentioned annealing separator, also has the role of reacting with the oxide layer mainly composed of silicon dioxide generated on the surface of the steel sheet during decarburization annealing to form a forsterite film, and the role of removing and purifying precipitates (such as part of precipitates such as AlN, MnS, MnSe, Si3N4, TiN, TiC, etc.) that control the growth of iron grains called inhibitors from the steel sheet during the final annealing process.

[0004] The forsterite film not only acts as a binder to improve the adhesion between the phosphate-based insulating film applied on the surface and the steel sheet, but also has a function of improving the magnetic properties by applying tension to the steel sheet. In addition, the purification of the above-mentioned inhibitors from the steel sheet plays an important role in reducing the magnetic properties of the grain-oriented electrical steel sheet, especially the iron loss.

[0005] As described above, magnesium oxide as an annealing separator plays a very large role in the properties of a grain-oriented electrical steel sheet in terms of both film properties and magnetic properties.

[0006] Therefore, various efforts have been made to improve the quality of magnesium oxide (magnesia), which is a main component of an annealing separator.

[0007] For example, Patent Document 1 discloses a technique for obtaining a good forsterite film by controlling the concentration of impurities such as CaO, SO 3 , and B, the specific surface area, the particle size, and the distribution of citric acid activity within a predetermined range.

[0008] In addition, since the final annealing is generally performed in a state where the steel sheet is wound into a coil, there are problems such as deterioration of the uniformity of the forsterite film or uneven purification of inhibitor components such as nitrogen and sulfur due to temperature deviations within the coil and uneven atmosphere permeability between layers of the steel sheet.

[0009] To solve this problem, for example, Patent Document 2 proposes coating 10 to 30 g / m 2 This is a method of applying a large amount of dense magnesium hydroxide.

[0010] In addition, Patent Document 3 proposes a technique of using magnesium oxide containing 1 to 20% of magnesium oxide of 100 mesh to 325 mesh as an annealing separator.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Publication No. 57-45472

[0014] Patent Document 2: Japanese Patent Publication No. 46-42703

[0015] Patent Document 3: Japanese Patent Application Laid-Open No. 49-126536 Summary of the invention

[0016] However, in the above-mentioned Patent Document 1, although there is an effect of being able to obtain a forsterite film with good uniformity, there is a problem that the magnetic properties are affected due to insufficient purification caused by the control of the nitridation amount of the steel sheet during annealing and the release of unnecessary inhibitor components such as nitrogen and sulfur in the steel into the atmosphere gas after secondary recrystallization.

[0017] In addition, Patent Documents 2 and 3 do not mention any means for purifying inhibitor components, so nitrogen, sulfur, etc. may not be sufficiently removed from steel by purification, resulting in deterioration of magnetic properties.

[0018] The present invention has been developed in view of the above-mentioned actual situation, and its purpose is to provide a powder for annealing separator and an advantageous method for manufacturing the same, which can improve the manufacturing yield by eliminating complex control factors, and can be manufactured inexpensively, and can be used in a method for manufacturing a oriented electromagnetic steel sheet with good uniformity of the film, good purification of impurities in the steel, and excellent magnetic properties.

[0019] In order to solve the above problems, the present inventors focused on the atmosphere permeability between steel plate layers wound into coils (between coil layers) and conducted intensive research on technologies for achieving good uniformity of forsterite film and purification of inhibitor components by optimizing the atmosphere permeability.

[0020] The results revealed the following new insights:

[0021] 1) The air permeability of the atmosphere between the steel coil layers at the temperature before the start of secondary recrystallization (final annealing) affects the magnetic properties and the purification of impurities.

[0022] 2) After the secondary recrystallization (final annealing) is completed, that is, the atmosphere permeability at an atmosphere temperature of 1000°C affects the purification caused by the diffusion of impurities such as nitrogen and sulfur into the annealing atmosphere.

[0023] The present invention is based on the above-mentioned findings.

[0024] That is, the gist of the present invention is as follows.

[0025] 1. A powder for annealing separator, which is used as an annealing separator in the production of grain-oriented electrical steel sheets, and contains magnesium oxide as a main component and has a nitrogen permeability of 0.020 cm / s to 0.50 cm / s.

[0026] 2. The powder for annealing separator according to item 1 above, wherein the content of the part not passing through a 166-mesh sieve is 0.5% by mass or less.

[0027] 3. A method for producing an annealing separator powder, which is the method for producing an annealing separator powder according to 1 or 2 above, wherein magnesium oxide having a citric acid activity of 300 seconds or more and containing 10% to 90% by mass of a 330-mesh unscreened portion is added in an amount of 5% to 50% by mass relative to the total amount of the annealing separator powder.

[0028] 4. A method for producing a grain-oriented electrical steel sheet, comprising using the powder for annealing separator according to 1 or 2 above.

[0029] According to the present invention, it is possible to inexpensively produce a powder for an annealing separator used as an annealing separator for producing a grain-oriented electrical steel sheet, which can obtain a grain-oriented electrical steel sheet having excellent film reactivity and good impurity purification of the steel sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a figure which shows the apparatus which measured the nitrogen permeability. DETAILED DESCRIPTION

[0031] Hereinafter, the experimental results leading to the present invention will be described.

[0032] First, a sample was prepared as follows.

[0033] As a starting material for preparing magnesium oxide, a vapor phase high-purity ultrafine powder magnesium oxide 2000A manufactured by Ube Material Industries, Ltd. was used. The purity thereof was 99.98%.

[0034] The starting material is hydrated with pure water to obtain magnesium hydroxide slurry, and the magnesium hydroxide slurry is pressed with a filter press to obtain a magnesium hydroxide filter cake.

[0035] 200 g of the magnesium hydroxide filter cake was placed in an alumina crucible and placed in an electric furnace (SPX1518T-17 manufactured by Maru Xiang Electric Co., Ltd.), and the electric furnace was reheated at a temperature of 600°C or 1000°C and then fired in air for 60 minutes. The fired product was directly cooled in the furnace and then crushed. After crushing, the particle size was adjusted using a sieve. The properties of the obtained magnesium oxide are recorded in Table 1.

[0036] Table 1

[0037]

[0038] The citric acid activity (CAA40) shown in Table 1 refers to the time (seconds) until the reaction is completed when magnesium oxide is added in excess to a 0.4N citric acid aqueous solution at a temperature of 30°C and stirred so that the final reaction rate is 40%. More specifically, the citric acid activity (CAA40) can be measured according to the citric acid activity measurement method described in Patent Document 1 under reaction conditions in which the final reaction rate of magnesium oxide is 40%.

[0039] The magnesium oxides listed in Table 1 were mixed in the amounts listed in Table 2 to obtain powders for annealing separators having different gas permeabilities.

[0040] Table 2

[0041]

[0042] It should be noted that, in the present invention, nitrogen permeability is used Figure 1 The described apparatus was measured as follows.

[0043] 4.0 g of the sample to be tested was weighed from the obtained annealing separator powder and pressed into a disc shape with an inner diameter of 30 mm and a height of 10 mm. The molded sample was placed on a glass filter (φ30 mm, pore size G1: JIS standard) set in the middle of a quartz tube as an experimental material. After the tube was placed in a vertical tubular furnace, nitrogen was supplied while adjusting the back pressure valve in such a way that the ventilation atmosphere became 100% nitrogen, and the nitrogen flow rate (mL / min) was measured when the atmosphere gas (N2) pressure before the experimental material passed was 10 kPa and the atmosphere gas pressure after the experimental material passed was 9 kPa (i.e., the differential pressure was 1 kPa). The measured nitrogen flow rate (mL / min) was substituted into the following calculation formula (1) to evaluate the nitrogen permeability.

[0044] As described above, the inventors of the present invention have found that the atmospheric permeability in the state of being coated between steel plate layers (between steel coil layers) before the start of secondary recrystallization is important, and have also established a test method that can evaluate the atmospheric permeability of the annealing separator powder in this state. Specifically, by molding a specified amount (4.0 g) of a sample into a test material of a specified volume (the volume of the above-mentioned disc-shaped material with an inner diameter of 30 mm × a height of 10 mm), it is possible to simulate the state in which the annealing separator prepared from the annealing separator powder is coated between steel plate layers. Furthermore, using the above-mentioned device provided with the test material, the atmospheric gas differential pressure before and after the test material is adjusted to a specified value (1 kPa), and then the nitrogen permeability at room temperature (25°C ± 1°C) is measured, thereby simulating the nitrogen permeability in the state in which the annealing separator is coated between steel plate layers before the start of secondary recrystallization. When annealing starts, the temperature in the furnace increases, and the annealing separator powder begins to sinter, and the gas permeability changes. However, if it is under the temperature conditions (800-1000°C) used to control the nitriding of the steel plate before the secondary recrystallization or under the temperature conditions of 1000°C after the completion of the secondary recrystallization, the above-mentioned sample pretreatment can be used to evaluate the nitrogen permeability at room temperature.

[0045] Therefore, the nitrogen permeability in the present invention is represented by the numerical value obtained by the above test.

[0046] Air permeability (cm / s) = gas flow rate (mL / min) ÷ (π × (φ (30mm) ÷ 2) 2 )×100÷60···Formula (1)

[0047] Next, the electromagnetic steel sheet billet containing C: 0.045 mass%, Si: 3.25 mass%, Mn: 0.070 mass%, Al: 80 massppm, N: 40 massppm and S: 20 massppm was heated to a temperature of 1200°C and then hot rolled to form a 2.0 mm thick hot rolled sheet coil. The hot rolled sheet coil was subjected to hot rolled sheet annealing at a temperature of 1000°C for 30 seconds, and the oxide scale on the surface of the steel sheet was removed. Next, the hot rolled annealed sheet was cold rolled by a tandem rolling mill to form a cold rolled sheet with a final cold rolled sheet thickness of 0.23 mm. Then, the cold rolled sheet was subjected to a decarburization annealing (also serving as a primary recrystallization annealing) at an aeration temperature of 850°C for 90 seconds, and the magnesium oxide powder described in Table 2 was applied as an annealing separator and then wound into a steel coil. The steel coil was subjected to final annealing (also serving as secondary recrystallization annealing) in which the steel coil was heated to 1200°C in a mixed atmosphere of 75 vol% nitrogen and 25 vol% hydrogen at a heating rate of 25°C / h and maintained at 1200°C in a hydrogen atmosphere of 100 vol% for 20 h, and then subjected to smoothing annealing to produce a sample steel sheet.

[0048] The uniformity of the film appearance of the sample steel sheets thus obtained, the concentrations of N and S in the steel sheets, and the repeated bending characteristics were investigated.

[0049] The uniformity of the film appearance was visually evaluated as excellent when the portion with different color tones accounted for 1% or less of the total surface area, good when it accounted for 5% or less, acceptable when it accounted for 20% or less, and unacceptable when it accounted for more than 20%.

[0050] The N and S concentrations in the steel sheet were measured after removing the film of the steel sheet by pickling. S was measured by the combustion-infrared absorption method (according to JIS G 1215-4 (2018)), and N was measured by the inert gas melting-thermal conductivity method. The repeated bending characteristics were measured using the method of JIS C 2553 (2019), and the ability to be bent 10 times or more was rated as good.

[0051] In addition, regarding the amount of impurities in the steel, a case where N: 15 mass ppm or less and S: 15 mass ppm or less were judged to be good.

[0052] Table 3 shows the magnesium oxide powder used in the experiment, the air permeability, the uniformity of the film appearance, the analysis values ​​of N and S remaining in the steel plate (mass ppm), and the number of repeated bending times.

[0053] As shown in Table 3, when the gas permeability of the magnesium oxide powder is low (No. 2-1, 2-3), the uniformity of the film appearance, the purification of impurities, and the number of repeated bendings caused by insufficient impurity purification are all poor. On the other hand, when the gas permeability of the magnesium oxide powder is too high (No. 2-6), the uniformity of the film appearance is deteriorated.

[0054] Table 3

[0055]

[0056] Next, the reasons for limiting each constituent element of the present invention will be described.

[0057] The annealing separator powder used as the object of the present invention contains magnesium oxide as a main component. Here, the main component refers to a powder containing 50% or more in mass%. If the magnesium oxide is less than 50 mass%, the formation of the forsterite film formed by the reaction of the internal oxide silicon dioxide formed during decarburization annealing and the magnesium oxide in the annealing separator is insufficient. Therefore, the proportion of magnesium oxide contained in 100 mass% of the annealing separator powder is preferably 60 mass% or more, and more preferably 80 mass% or more. The upper limit is not particularly limited and can be 100 mass%.

[0058] In addition, the annealing separator powder of the present invention has magnesium oxide as a main component, but the remainder thereof can be used well as long as it is a powder used in the conventionally known annealing separator powder. The powder that can be used well is, for example, calcium oxide, silicon oxide, magnesium phosphate, calcium phosphate, titanium oxide, boron oxide, sodium borate, magnesium hydroxide, calcium hydroxide, strontium hydroxide, aluminum hydroxide, magnesium sulfate, calcium sulfate, strontium sulfate, aluminum sulfate, etc. These can be used alone or in combination.

[0059] In addition, although industrially inevitable impurities are also contained, the maximum amount of such inevitable impurities is about 5.0 mass %.

[0060] In order to promote uniformity of film appearance and purification of inhibitor components in steel, the nitrogen permeability of the annealing separator powder of the present invention when applied between steel sheets before the start of secondary recrystallization is in the range of 0.020 cm / s to 0.50 cm / s.

[0061] This is because, in order to stabilize the secondary recrystallization generated during the final annealing, it is necessary to perform annealing under conditions satisfying a temperature before the start of secondary recrystallization of around 800° C. and an atmosphere containing nitrogen, thereby appropriately increasing the amount of nitrogen in the steel.

[0062] That is, since the steel sheet is wound into a coil and annealed, the increase in nitrogen at the edge and center of the coil is different, and the secondary recrystallization state is different. Therefore, the nitrogen permeability in the state of coating between the steel sheets before the start of secondary recrystallization must be 0.020 cm / s or more. On the other hand, if the increase in nitrogen is too much, the amount of purification caused by the release of nitrogen from the steel into the atmosphere at a temperature exceeding 1000°C is insufficient, resulting in an excessive amount of nitrogen residue. Therefore, the nitrogen permeability in the state of coating between the steel sheets before the start of secondary recrystallization is 0.50 cm / s or less. From the viewpoint of appearance uniformity, it is preferably 0.030 cm / s or more, and more preferably 0.050 cm / s or more. In addition, it is preferably 0.30 cm / s or less, and more preferably 0.20 cm / s or less.

[0063] It should be noted that if the annealing separator powder contains more coarse particles than necessary, scratches and indentations may occur on the surface of the steel sheet. Therefore, in the present invention, the unscreened portion of the 166 mesh sieve is preferably 0.5% by mass or less, more preferably 0.4% by mass or less, and further preferably 0.3% by mass or less. The details of the method for measuring the unscreened portion will be described later.

[0064] The method for manufacturing the powder for annealing separator of the present invention is not particularly limited, and conventional methods can be used except for the method specified in the present invention. Among them, it is preferred to use a substance that forms magnesium oxide by firing a raw material as the main component, and as its raw material, magnesium hydroxide, magnesium carbonate, and magnesium chloride can be cited. These can be used alone or in combination. For example, magnesium hydroxide slurry is prepared from these raw materials, and the water content of the obtained slurry is squeezed with a filter press to obtain a filter cake. The filter cake is fired at a high temperature (about 950 to 1200° C.), and the fired product obtained is crushed to obtain magnesium oxide powder.

[0065] The simplest method for controlling nitrogen permeability is to adjust the particle size distribution, but other methods include controlling the amount of chlorine, boron, phosphorus, etc. in magnesium oxide and mixing magnesium oxides with different sintering properties. Alternatively, it can be carried out by combining any two or more of these methods.

[0066] The particle size of the annealing separator powder in the present invention does not need to be adjusted using only magnesium oxide as the main component, but can also be adjusted by mixing the above-mentioned powders used well as the remainder, such as powders of pre-controlled particle sizes of compounds such as calcium oxide, calcium hydroxide, silicon oxide, magnesium phosphate, and calcium phosphate.

[0067] For example, when the air permeability is controlled by controlling the particle size distribution of magnesium oxide, in order to maintain the nitrogen permeability after the completion of the secondary recrystallization, it is preferred to include magnesium oxide with a large particle size. Specifically, it is preferred that the magnesium oxide containing 10% to 90% by mass of the unscreened portion of the 330 mesh sieve contains 5% to 50% by mass relative to the entire annealing separator powder (i.e., 100% by mass).

[0068] At this time, by suppressing the citric acid activity (CAA40) of the raw material powder (magnesium oxide) to a lower level (i.e., the value of CAA40 becomes larger), the change in the particle size of the powder is reduced, and the reduction in gas permeability at high temperature can be avoided. Therefore, CAA40 is preferably 300 seconds or more, more preferably 400 seconds or more, and further preferably 480 seconds or more. On the other hand, if CAA40 exceeds 1400 seconds, the reactivity with the silicon dioxide on the surface of the steel plate becomes too low, and the unit area weight of the forsterite film becomes less. Therefore, CAA40 is preferably 1400 seconds or less, more preferably 1100 seconds or less, and further preferably 950 seconds or less.

[0069] The citric acid activity (CAA40) of magnesium oxide can be controlled by appropriately adjusting the firing temperature and time according to its raw materials (magnesium carbonate, magnesium hydroxide, magnesium chloride, etc.) during production. More specifically, the higher the firing temperature and the longer the firing time, the greater the value of the citric acid activity.

[0070] The steel sheet used in the present invention is not particularly limited in type as long as it is a grain-oriented electrical steel sheet having a coating mainly composed of forsterite on the surface. Generally, such a grain-oriented electrical steel sheet is manufactured by hot rolling a silicon-containing steel billet by a known method, processing it to a final sheet thickness by one or multiple cold rollings with intermediate annealing, then performing a recrystallization annealing, and then applying an annealing separator and performing final annealing.

[0071] In addition, if the thickness of the steel plate is reduced, the proportion of the surface that contributes to the performance of the steel plate increases, and the influence of the atmosphere permeability is more significantly manifested. Therefore, the magnesium oxide of the present invention, especially when applied to a thin steel plate with a thickness of 0.23 mm or less, exerts an excellent effect compared with the conventionally known magnesium oxide.

[0072] Example

[0073] (Example 1)

[0074] Basic magnesium carbonate (MgCO3)4Mg(OH)2·xH2O manufactured by NACALAI TESQUE, INC. was used as a starting material, diluted with pure water to a slurry state, and the slurry was pressed with a filter press to obtain a filter cake. Next, the filter cake was placed in an alumina crucible and fired in a box furnace in air at the temperature described in Table 4 for 40 minutes. The fired filter cake was crushed and the particle size was adjusted using a sieve to obtain powder raw materials 4-1 to 4-10 for annealing separators. The particle size was adjusted by placing five metal JIS standard sieves (Φ200 mm) of 500 mesh (mesh size 25 μm), 390 mesh (mesh size 38 μm), 330 mesh (mesh size 45 μm), 166 mesh (mesh size 90 μm), and 140 mesh (mesh size 106 μm) in order from the bottom on a sieving machine (OCTAGON 200 manufactured by Seishin Enterprise Co., Ltd.), putting 1 kg of the crushed material in, and performing dry sieving for 60 minutes at the maximum vibration mode, and the unscreened portion was used as an indicator.

[0075] In addition, magnesium chloride hexahydrate manufactured by NACALAI TESQUE, INC. was dissolved in pure water maintained at 25° C. to prepare a saturated aqueous solution. Next, the saturated aqueous solution was reacted with calcium hydroxide to prepare magnesium hydroxide. The magnesium hydroxide thus obtained was filtered and washed with water, and then put into pure water again to prepare a magnesium hydroxide slurry. The slurry was pressed with a filter press to obtain a filter cake. Next, the filter cake was placed in an alumina crucible and fired in a box furnace in air at the temperature described in Table 4 for 40 minutes. After the fired filter cake was crushed, the particle size was adjusted using a sieve to obtain powder raw materials 4-11 to 4-16 for annealing separators.

[0076] The annealing separator powder raw materials prepared in this way were mixed as shown in Table 5 to prepare annealing separator powders having various air permeabilities.

[0077]

[0078]

[0079] Next, a silicon steel billet consisting of C: 0.06 mass%, Si: 2.95 mass%, Mn: 0.07 mass%, S: 0.015 mass%, Sb: 0.015 mass% and Cr: 0.03 mass%, and the remainder Fe and inevitable impurities is heated at 1350°C for 40 minutes, hot rolled to form a plate thickness of 2.6 mm, then hot-rolled plate annealing is performed at 900°C and 60 seconds, and then cold rolled with intermediate annealing at 1050°C and 60 seconds to a final plate thickness of 0.23 mm to produce a steel plate.

[0080] After decarburization annealing was performed on the steel sheet, the powders listed in Table 5 were applied as annealing separators, respectively, and then a final annealing was performed by heating to 1200°C at a heating rate of 25°C / h in a mixed atmosphere of 75 vol% nitrogen and 25 vol% hydrogen and maintaining it at 1200°C for 20 h in a hydrogen 100 vol% atmosphere, and further smoothing annealing was performed to produce the sample of this embodiment.

[0081] The uniformity of the film appearance, the length ratio (%) of scratch and indentation generation, the concentrations of N and S in the steel sheet, and the repeated bending characteristics of the samples thus obtained were investigated.

[0082] The uniformity of the film appearance was visually evaluated as excellent when the portion with different color tones accounted for 1% or less of the total surface area, good when it accounted for 5% or less, acceptable when it accounted for 20% or less, and unacceptable when it accounted for more than 20%.

[0083] The scratch and indentation length ratio (scratch and indentation generation rate) is preferably 5.0% or less, and particularly preferably 1.0% or less. The scratch and indentation generation rate is the length of the steel sheet measured in the rolling direction per m. 2 The length of the portion with two or more scratches and indentations is expressed as a ratio to the total length of the steel sheet or coil.

[0084] The N and S concentrations in the steel plate were measured by a combustion-infrared absorption method after removing the film of the steel plate by pickling, and the N concentration was measured by an inert gas fusion-thermal conductivity method.

[0085] The repeated bending property was measured using the method of JIS C 2553 (2019), and the property was evaluated as good if it could be bent 10 times or more.

[0086]

[0087] As shown in Table 6, in the case of the annealing separator with low air permeability (No. 5-1, 5-2, 5-3), the film appearance was uniform, impurity purification was insufficient, and the number of repeated bendings caused by insufficient impurity purification was poor. On the other hand, in the case of the annealing separator having the desired nitrogen gas permeability, the film appearance uniformity, impurity purification and repeated bending characteristics were excellent, and in particular, when the unscreened portion (166 mesh) was 0.5 mass% or less, the scratch and indentation generation rate was 1.0% or less, which was a very good result.

[0088] (Example 2)

[0089] Calcium oxide (average particle size 45 μm), silicon oxide (average particle size 60 μm), and magnesium phosphate (average particle size 53 μm) with different particle sizes were mixed with magnesium oxide No. 1-1 in Table 1 at the ratios described in Table 7 to prepare an annealing separator powder containing magnesium oxide having air permeability described in Table 7.

[0090] Next, the electromagnetic steel sheet material containing C: 0.045 mass%, Si: 3.25 mass%, Mn: 0.070 mass%, Al: 120 massppm, N: 50 massppm, S: 40 massppm was heated to 1200°C and then hot-rolled to produce a 2.0 mm thick hot-rolled sheet coil, which was then hot-rolled at 1000°C for 30 seconds to remove the oxide scale on the surface of the steel sheet. Next, cold rolling was performed by a tandem rolling mill to produce a steel sheet with a final cold-rolled sheet thickness of 0.20 mm.

[0091] The steel plate was subjected to decarburization annealing at an equalizing temperature of 850°C for 90 seconds, 5.0 g of titanium oxide was mixed with 100 g of the powder (No. 1 to 11) listed in Table 7, the resultant was applied as an annealing separator and wound into a steel coil, and a final annealing was performed by heating to 1200°C at a heating rate of 25°C / h in a mixed atmosphere of 75 vol% nitrogen and 25 vol% hydrogen and maintaining it at 1200°C for 20 h in an atmosphere of 100 vol% hydrogen, and further smoothing annealing was performed to produce a sample of the present embodiment.

[0092] The uniformity of the film appearance, the length ratio (%) of scratch and indentation generation, the concentrations of N and S in the steel sheet, and the repeated bending characteristics of the samples thus obtained were investigated.

[0093] The uniformity of the film appearance was visually evaluated as excellent when the portion with different color tones accounted for 1% or less of the total surface area, good when it accounted for 5% or less, acceptable when it accounted for 20% or less, and unacceptable when it accounted for more than 20%.

[0094] The scratch and indentation length ratio is preferably 5.0% or less, and particularly preferably 1.0% or less.

[0095] The N and S concentrations in the steel plate were measured by a combustion-infrared absorption method after removing the film of the steel plate by pickling, and the N concentration was measured by an inert gas fusion-thermal conductivity method.

[0096] The repeated bending property was measured using the method of JIS C 2553 (2019), and the property was evaluated as good if it could be bent 10 times or more.

[0097]

[0098] As shown in Table 7, when the air permeability of the annealing separator is small (No. 1), the uniformity of the film appearance, the purification of impurities, and the number of repeated bendings caused by the insufficient purification of impurities are poor. In addition, when the amount of magnesium oxide used is 40 g (i.e., the ratio in the annealing separator is 40 mass%; No. 10, 11), the nitrogen permeability of the annealing separator cannot be controlled within the range desired in the present application, N purification is insufficient, and the uniformity of the film appearance and the repeated bending characteristics are poor. On the other hand, in the case of an annealing separator having the desired air permeability, the uniformity of the film appearance, the purification of impurities, and the repeated bending characteristics are excellent, and in particular, when the unscreened portion (166 mesh) is 0.5 mass% or less, the scratch and indentation generation rate is 1.0% or less, which is a very good result.

Claims

1. A powder for annealing separator, which is used as an annealing separator in the production of grain-oriented electrical steel sheets, contains 50% by mass or more of magnesium oxide, has a nitrogen permeability of 0.020 cm / s to 0.50 cm / s, wherein: The nitrogen permeability is calculated as follows: 4.0 g of the annealing separator powder was pressed into a disk with an inner diameter of 30 mm and a height of 10 mm, and placed in a φ30 mm glass filter provided in the middle of a quartz tube. 100% nitrogen was passed through the filter at room temperature of 25°C±1°C. The nitrogen flow rate when the pressure difference before and after the filter became 1 kPa was substituted into the following calculation formula (1) to calculate the nitrogen permeability. Air permeability = gas flow rate ÷ (π × (φ (30mm) ÷ 2) 2 )×100÷60…Formula (1) Wherein, the unit of air permeability is cm / s, and the unit of gas flow rate is mL / min.

2. The powder for annealing separator according to claim 1, wherein The fraction not passing through a 166-mesh sieve was 0.5% by mass or less.

3. A method for producing an annealing separator powder, which is the method for producing an annealing separator powder according to claim 1 or 2, wherein 5% to 50% by mass of magnesium oxide having a citric acid activity of 300 seconds to 1400 seconds and containing 10% to 90% by mass of a 330-mesh sieve-unscreened portion is added to the entire annealing separator powder, wherein: The citric acid activity refers to the time until the reaction is completed when the magnesium oxide is added in an excess amount so that the final reaction rate becomes 40% in a 0.4N citric acid aqueous solution at a temperature of 30° C. and stirred. 4 . A method for producing a grain-oriented electrical steel sheet, comprising using the annealing separator powder according to claim 1 .

Citation Information

Patent Citations

  • JP1974126536A

  • Forming method for forsterite insulation film of anisotropic silicon steel plate

    JP1982045472B2

  • Bismuth oxyhalide photocatalyst with hierarchical structure and preparation method thereof

    CN110104684A

  • Magnesium oxide for oriented silicon steel annealing separant, and preparation method

    CN111186850A